2014
DOI: 10.1016/j.enggeo.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the slow-moving landslides in Jurassic red-strata in the Three Gorges Reservoir, China

Abstract: Landslides in Jurassic red-strata make up a great part of geohazards in the Three Gorges Reservoir (TGR) in China. Most of them begin to move slowly with the accumulated displacement increasing stepwise, which corresponds to seasonal rainfall and 30 meters of reservoir water level fluctuation (145 m to 175 m on elevation). We analyzed the movement of 21 slow moving landslides in Jurassic red-strata in TGR, and found that all these landslides involved in two differing processes; one is the sliding process with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…The results suggested that rainfall and the reservoir water level were the principal factors influencing the deformation of the rock mass (Xia et al, 2013). Other similar works corroborate these results: an increase in water pore pressure increases the likelihood of a landslide (Zangerl et al, 2010;Zhu et al, 2012;Wei et al, 2013;Miao et al, 2014).…”
Section: Introductionmentioning
confidence: 65%
“…The results suggested that rainfall and the reservoir water level were the principal factors influencing the deformation of the rock mass (Xia et al, 2013). Other similar works corroborate these results: an increase in water pore pressure increases the likelihood of a landslide (Zangerl et al, 2010;Zhu et al, 2012;Wei et al, 2013;Miao et al, 2014).…”
Section: Introductionmentioning
confidence: 65%
“…The As is well known [31,32], the ground water table or pore-water pressure within the soil layers of the landslide body are affected by the reservoir surface fluctuation and local precipitation, which decreases the effective normal stress leading to a decrease in shear strength of the soils. In previous studies, the fluctuation of the reservoir water level and seasonal rainfall are found as the two main triggering factors for landslides along the Yangtze River banks [31,[33][34][35][36].…”
Section: The Relationship Between the Landslide And Water Level Variamentioning
confidence: 99%
“…The change in displacement rate between these two periods might be triggered by the consecutive rainfall in the summer of 2008. Water level fluctuations and rainfall are the two most important impact factors of slope stabilities in the Three Gorges region for slopes near the river [16]. The upstream water level of Three Gorges and rainfall records from Badong and Fengjie were used to investigate the relationship between displacements and water level fluctuation/rainfall.…”
Section: Impact Factors For Landslide Activitiesmentioning
confidence: 99%
“…As we can see from Figure 11c, the landslides located at P4 experienced stepwise displacements. The landslides in the Three Gorges areas with stepwise displacement progression mainly undergo two main processes: the sliding process and the dormant process [16]. During the sliding process, the landslide moves at inconsistent rates, whereas during the dormant stage, shear strength has been recovered and stability is achieved for some duration of time.…”
Section: Impact Factors For Landslide Activitiesmentioning
confidence: 99%
See 1 more Smart Citation